Patterns of Recovery From Aphasia in the First 2 Weeks After Stroke - Wilson, Stephen M. (J Speech Lang Hear Res, 2019)
PURPOSE: Recovery from aphasia after stroke has a decelerating trajectory, with the greatest gains taking place early and the slope of change decreasing over time. Despite its importance, little is known regarding evolution of language function in the early postonset period. The goal of this study was to characterize the dynamics and nature of recovery of language function in the acute and early subacute phases of stroke. METHOD: Twenty-one patients with aphasia were evaluated every 2–3 days for the first 15 days after onset of acute ischemic or hemorrhagic stroke. Language function was assessed at each time point with the Quick Aphasia Battery (Wilson, Eriksson, Schneck, & Lucanie, 2018), which yields an overall summary score and a multidimensional profile of 7 different language domains. RESULTS: On a 10-point scale, overall language function improved by a mean of 1.07 points per week, confidence interval [0.46, 1.71], with 19 of 21 patients showing positive changes. The trajectory of recovery was approximately linear over this time period. There was significant variability across patients, and patients with more impaired language function at Day 2 poststroke experienced greater improvements over the subsequent 2 weeks. Patterns of recovery differed across language domains, with consistent improvements in word finding, grammatical construction, repetition, and reading, but less consistent improvements in word comprehension and sentence comprehension. CONCLUSION: Overall language function typically improves substantially and steadily during the first 2 weeks after stroke, driven mostly by recovery of expressive language. Information on the trajectory of early recovery will increase the accuracy of prognoses and establish baseline expectations against which to evaluate the efficacy of interventions. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.7811876